FUNGSI PENGAWASAN DEWAN PERWAKILAN RAKYAT (DPR) TERHADAP PENGELOLAAN KEUANGAN DAERAH - Bawole, Deisy (LEX ADMINISTRATUM, 2015)
In the framework of the implementation of the regional government, as where stipulated in Law No. 23 Year 2014 on Regional Government, followed by the financial balance between the central government and local government, Law No. 33 of 2004 on the financial balance between the central government and local government, arising rights and obligations of areas that can be assessed with the money that needs to be managed in a system of financial management. Financial management of the area is the whole of activities that includes planning, implementation, pentausahaan, reporting, accountability and financial control area. Regional Representatives Council (DPRD) as an element of local governance that aims to continue the people's aspiration to build a prosperous society. Parliament has the duty and authority to supervise the implementation of local regulations and other laws and regulations, and have policies in implementing regional development programs. Oversight of Parliament in accordance with the rules should be more focus on monitoring the implementation of the budget. One satua spec that are very important in the management of the financial area is the effectiveness of the oversight on financial management, conducted both internally and externally, the effectiveness of the oversight role becomes crucial in order to achieve financial governance is good and right on target for people (Good Financial Governance).